MIGRATION AND THE TRANS-NATIONALISATION OF AFRICAN PENTECOSTALISM IN EUROPE: ENCOUNTER AND PROSPECTS - Olorunnisola, Titus S. (Advances in Social Sciences Research Journal, 2020)
Migration, the movement of people from one geographical location to another is an indispensable component of globalisation which has impacted the latter with visible effects. Neo-Pentecostal Christian movements from different parts of Africa have seized the advantage of both migration and globalization to advance their missionary causes. This has resulted in planting new churches and organization of para-church ministries and outreaches in different parts of Europe and elsewhere. Using the Critical Integrated Analysis (CIA) method, which seeks to generate data from the existing body of knowledge, the article explored the trajectories of African migration vis-à-vis the penetration of African-led Pentecostal churches in some part of Europe. This process has stemmed encounters between the European and African cultures plus the hurdle of navigating the cultural nuances of the Europeans. The article discovered that although there are shreds of evidence of growth among African-led migrant churches, more grounds need to be covered. It suggested that migrant churches need to structure their ministries and organisations in ways that propel appropriate cultural engagement with their host communities to enable them to influence and transform their immediate social realities.